Implications of COVID‐19 Regulations for People With Visual and Intellectual Disabilities: Lessons to Learn From Visiting Restrictions. Issue 1 (22nd October 2021) - Honingh, Aline K.; Koelewijn, Angelique; Veneberg, Bert; ter Horst, Francis; Sterkenburg, Paula S.
Abstract: Background: Due to the COVID‐19 pandemic, governments of many countries announced regulations to prevent the virus from spreading. For people with a disability living in a sheltered care facility in the Netherlands, this meant that they were not able to receive any visitors for almost 3 months. Aim: This study examines how people with an intellectual and visual disability and their families experienced the period in which it was mandated not to have any physical contact. The aim is to examine the experiences of this target group and gain insight in the way measures were taken in order to be able to advise care organizations about adequate care with respect to possible restrictive measures in the future. Methods: In‐depth interviews were conducted with two groups of people: (1) fourteen people with an intellectual and visual disability, living in sheltered care facilities and (2) twelve people being relatives of residents of these same sheltered care facilities. In the interviews, the participants were questioned about their experiences with respect to the adjusted visiting regulations and with respect to the relation with their family during this period. A thematic analysis was performed first separately and then combined. Results and Discussion: A number of themes resulted from the analysis that were related to (1) the instructed regulations of the sheltered care facilities and the government; (2) the relation with family and friends; and (3) the consequences of COVID‐19 and the regulations. Both relatives and residents were understanding of the difficult situation, but also expressed criticism about the chosen regulations, the communication thereof, and the practical implementation. Both groups have experienced the interruption of close contact as emotional and difficult. However, also positive consequences of the restrictions due to COVID‐19 were mentioned. The results provide a list of recommendations for sheltered care facilities.